Single-step growth of MoO3 nanorods via magnetron sputtering. Issue 3 (16th December 2022) - Gudena, Gutema Teshome; Cho, Hyeon Ho; Megersa, Daba Deme; Lee, Jaeyeong; Bae, Jong Seong; Yu, Hak Ki
Abstract : Single-step growth of (0 h 0)-oriented MoO3 nanorods via radio frequency sputtering for humidity sensors. Abstract : Uniformly distributed crystalline α-molybdenum oxide nanorods (NRs) were grown on c -plane sapphire substrates using a single-step radio frequency sputtering technique. The shape and size of the NRs can be controlled by regulating the composition of the sputtering gas (Ar : O2 mixture). A pin-like nanowire structure was observed at an Ar : O2 ratio of 20 : 0, which transformed to NRs at Ar : O2 ratios of 20 : 2 and 20 : 4. Additionally, the length of the NRs increased with an increase in the deposition time. X-ray diffraction and transmission electron microscopy analyses indicated the highly crystalline nature of the NRs. X-ray photoelectron spectroscopy measurements revealed that the NRs were composed of nearly stoichiometric α-MoO3 . Humidity sensing experiments indicated that the as-grown α-MoO3 NRs have good sensitivity to moisture.